Antecedents and outcomes of unethical pro-organizational behaviors in Pakistan’s retail sector - Aneeq, Inam (2022)
Employees in a highly competitive corporate setting may engage in unethical behavior such as lying, providing inaccurate information to stakeholders, or concealing information from customers to benefit the organization. Such actions are known as unethical pro-organizational behaviors (UPB). These actions have resulted in penalties, product withdrawals, and company bankruptcies. Despite these negative effects, the reasons employees engage in such behavior and the outcomes remain under-explored. Thus, the objective of this study was to examine the antecedents and outcomes of UPB. This study adopted a quantitative research paradigm in which the data was collected in two waves from 450 employees working in the marketing or sales departments of the retail sector in Pakistan. The sample of this study was chosen based on quota sampling in which quota was allocated for the most populated cities of Punjab, Pakistan. Data were analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM). The findings revealed the prominent influence of peer’s ethicality which was found to have a negative influence on UPB. Other antecedents such as relative leader-member exchange, job embeddedness, and moral disengagement were also reported to be positively related to UPB. Moreover, the significant mediating result of guilt indicated that UPB induced guilt which then led to turnover intention and decreased job satisfaction. However, the positive relationship between moral disengagement and UPB was strengthened when the leader’s bottom-line mentality was low but weakened when leader’s bottom-line mentality was high. The result also demonstrated that UPB induced more guilt when the employees were more morally aware. The limitation of this study is based on studying the phenomenon of UPB in the context of retail stores in Punjab province in Pakistan and the use of quota sampling due to the unavailability of the sampling frame. Despite the limitations, the findings extend the understanding of the reasons and outcomes of UPB and offer theoretical and practical implications.